Fluidization dynamics of hydrophobic nanosilica with velocity step changes - Al-Ghurabi, Ebrahim H.; Asif, Mohammad; Siva Kumar, Nadavala; Khan, Sher Afghan (MDPI, 2020)
Nanosilica is widely used in various applications, with its market expected to grow over USD 5 billion by 2025. The fluidized bed technology, owing to its intimate contact and efficient mixing of phases, is ideally suited for the large scale processing of powders. However, the bulk processing and dispersion of ultrafine nanosilica using the fluidized bed technology are critically affected by the interparticle forces, such that the hydrophilic nanosilica shows agglomerate bubbling fluidization (ABF), while the hydrophobic nanosilica undergoes agglomerate particulate fluidization (APF). This study carried out a detailed investigation into the fluidization hydrodynamic of the hydrophobic nanosilica by monitoring the region-wise dynamics of the fluidized bed subjected to a regular step change of fixed duration in the gas velocity. The gas flow was controlled using a mass controller operated with an analog output signal from a data acquisition system. The analog input data were acquired at the sampling rate of 100 Hz and analyzed in both time and temporal frequency domains. The effect of velocity transients on the bed dynamics was quickly mitigated and appeared as lower frequency events, especially in regions away from the distributor. Despite the apparent particulate nature of the fluidization, strong hysteresis was observed in both pressure drop and bed expansion. Moreover, the fully fluidized bed’s pressure drop was less than 75% of the theoretical value even though the bed appeared to free from non-homogeneities. Key fluidization parameters, e.g., minimum fluidization velocity (Umf) and the agglomerate size, were evaluated, which can be readily used in the large scale processing of nanosilica powders using fluidized bed technology.